APLICACIÓN DE NORMAS DE SEGURIDAD ELÉCTRICA Y SU EFICACIA EN EL AHORRO ENERGÉTICO DENTRO DE LA UNIVERSIDAD NACIONAL DE CHIMBORAZO (CAMPUS LA DOLOROSA). - Márquez Sañay, Galo Fabián (2016)
Taking into account the cost and the energy crisis that our country is facing nowadays, we have seen the need of applying a project the electric consumption, just like the outcomes at “Universidad Nacional de Chimborazo” campus “La Dolorosa”. The project details causes; effects and impacts, as well as the possible strategies that will help to optimize the use of the electric power by means of a saving norm. A budget reduction has not allowed that the different companies and educational institutions carry out necessary steps for the electric system operation, which regularly presents problems. The current project of energy saving is aimed to the “Universidad Nacional de Chimborazo” campus “La Dolorosa” due to the overriding need to solve the inconvenient mentioned before. This normative sample shows the due alternatives for the electric power saving for concept of illumination, since they affect directly the energy conception at UNACH, as well as on the understanding in the use of the energy.